Characteristics of Cerebrospinal Fluid in Tuberculous Meningitis Patients with Hydrocephalus - Astrid Tamara Maajid Budiman; Nida Suryana; Ahmad Faried; Ida Parwati (Faculty of Medicine Universitas Padjadjaran, 2018)
Objective: To describe cerebrospinal fluid (CSF) characteristics in tuberculous meningitis (TBM) with hydrocephalus patients as diagnostic criteria of TBM.Methods: A cross-sectional using retrospective method was applied in this study by obtaining medical records of TBM with hydrocephalus patients that were treated at Department of Neurosurgery Dr. Hasan Sadikin General Hospital, Bandung from January 2014–September 2016. Results: Sixty one records were included in the study. Patient characteristics such as age, gender, and CSF laboratory features such as color and clarity, cells and differential count, protein, and glucose were recorded and descriptively analyzed. The majority of CSF macroscopic appearance was seen to be clear (88%) and colorless (88%). Median for CSF cell count was 25 cells/mm3 with lymphocyte predominance (median: 76%). Increased protein from normal value range was seen in CSF (median: 50 mg/dL) while the mean for CSF glucose in this study remained in its normal value range (mean: 58.9±26.68 mg/dL) with lower CSF to blood glucose ratio (mean: 0.41±0.27).Conclusions: Clear CSF with colorless appearance, lymphocyte pleocytosis, high protein level, and low CSF glucose as well as blood glucose ratio remain typical CSF characteristics of TBM patients found at the Department of Neurosurgery, Dr. Hasan Sadikin General Hospital, Bandung. Keywords: Cerebrospinal fluid, hydrocephalus, tuberculous meningitis DOI: 10.15850/ijihs.v6n2.1129